The evaluation of online school examination implementation using CIPP model - Sapto Irawan; Danu Prasetyo (Graduate School, Universitas Negeri Yogyakarta, 2020)
This study aims to evaluate the implementation of online school exam conducted at SMK PGRI 1 Salatiga in 2019/2020 Academic Year. This study is descriptive evaluation research using CIPP (Context, Input, Process, Product) model. The research focuses on conducting evaluation activities through four-component aspects (Context, Input, Process, and Product evaluation). Data were collected through (1) interviews with the Principal, Deputy Principal for Curriculum, School Examination Committee, and (2) documentation study, conducted by collecting data information related to the implementation of the online school exams at SMK PGRI 1 Salatiga. This study involved 194 subjects consisting of 181 school exam participants and 13 school exam committees at SMK PGRI 1 Salatiga. This evaluation research results can be seen through the four aspects of evaluation component, namely (1) Context in the implementation of online School Exams has been based on a Circular from the Minister of Education and Culture and the Office of Education and Culture of Central Java Province. (2) Inputs in the implementation of online School Exams are in accordance with the planning criteria in implementing school exams, including online application preparation, school exam planning and schemes, network preparation, Standard Operating Procedures (SOP) as committee test organizers. (3) The process of organizing online school exams goes well, but there are technical problems experienced by school exam participants related to internet network. (4) The product in organizing online school exams is in a quite good category, indicated by the results of online school exams carried out in a relatively short time.